Chart of the N.W. coast of America and the N.E. coast of Asia, explored in the years 1778 and 1779. - Roberts, Henry (Wm. Faden, 1794)
Map shows routes of Captain James Cook in 1778 and 1779 during exploration of the northwestern part of North America [present-day Alaska]. Coastlines, settlements, and areas of indigenous population in North America and northeast Asia are noted. Includes historical notes. Relief shown pictorially. Depths shown by soundings. Scale [ca. 1:10,137,600].